2011
DOI: 10.3892/ol.2011.420
|View full text |Cite
|
Sign up to set email alerts
|

Histologic coagulative tumour necrosis as a prognostic indicator of aggressiveness in renal, lung, thyroid and colorectal carcinomas: A brief review

Abstract: Abstract. Tumour growth involves two essential deviations from the normal state including the induction of proliferative stimuli, and simultaneous suppression of potentially compensatory cell death. It has been suggested that the development of invasive cancer involves a progressive switch from predominantly apoptotic to necrotic tumour cell death. The presence of tumour necrosis in pathologic specimens may not only reflect tumour biology, but also provide additional beneficial prognostic information. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Mechanisms similar to coagulative necrosis might speculatively act at the centers of rapidly growing solid tumors to promote tumor growth by neovasularization, 15,16 although this is speculative.…”
Section: Morphological Aspects Of Necrosismentioning
confidence: 99%
“…Mechanisms similar to coagulative necrosis might speculatively act at the centers of rapidly growing solid tumors to promote tumor growth by neovasularization, 15,16 although this is speculative.…”
Section: Morphological Aspects Of Necrosismentioning
confidence: 99%
“…In 34 cases, specimen was procured using CT guidance, in 12 cases via bronchoscopy, and in 1 case using ultrasound guidance. In 21 cases (CT guided [16] cases and endobronchial [5] cases), paired FNA and NCB specimens were obtained, in 18 cases (CT guided [16], endobronchial [1], and USG [1]) only NCB were obtained and in 8 cases (CT guided [2], endobronchial [6]) only FNA was available. Knowledge of clinical history and/or previous cytological or histological material was available for review in 39 cases, due to which either none or at most 2 immunostains were performed to attain a definitive diagnosis in 30 cases (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, all 8 cases had elongated columnar cells but necrosis was seen (focal or extensive) in only 2 cases. Besides, necrosis can be seen in primary carcinomas of the lung as well, most commonly squamous cell and large cell undifferentiated carcinoma thereby undermining its utility . Also of note is that the features described above only suggest colorectal differentiation but not a colorectal primary, as WHO has recently recognized pulmonary adenocarcinoma with enteric differentiation (PAED) as a rare subtype of lung adenocarcinoma classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two separate studies have shown that ctDNA was more likely to be detected among patients with squamous cell carcinoma than adenocarcinoma (27,28). This is thought to be due to a higher rate of tumor necrosis and passive DNA release among patients with squamous cell carcinoma.…”
Section: Next Generation Sequencingmentioning
confidence: 98%